Cross-cultural adaptation of the instrument "tool to estimate patient's costs" in priority municipalities of Brazil in tuberculosis control - Gabriela Ferreira Nunes; Leticia Molino Guidoni; Eliana Zandonade; Leticya dos Santos Almeida Negri; Ethel Leonor Noia Maciel (Universidade Federal do Rio de Janeiro, 2018)
Abstract Introduction: Tuberculosis is historically associated with poverty, generating costs that can influence treatment. Considering the impact of the costs of illness, the importance of adapting the instrument is highlighted. Objective: To adapt transculturally to Brazilian Portuguese the instrument Tool to Estimate Patient's Costs. Methods: Study of the type transcultural adaptation of instrument. The translation followed the criteria described by Herdman, 1998, in order to preserve functional equivalence as much as possible. The questionnaire with cross-cultural adaptation was applied to 77 patients, with at least one full month of treatment for the disease. Results: Instrument was shown with Cronbach Alpha above 0.71 constituting a good tool for measuring the costs of the disease, being necessary modifications. Conclusions: This study suggests the creation of an instrument adapted for the treatment of TB in Brazil, for the evaluation of costs with the illness by tuberculosis.